Carbapenem-Resistant Klebsiella pneumoniae in Healthcare-Associated Infections: Global and Regional Epidemiology, Resistance Mechanisms, and Therapeutic Strategies, with Particular Attention to Romania and Eastern Europe (2020–2025) - Oana-Elena Ioniţă; Roxana-Carmen Cernat; Nicola-Maria Militaru; Maria-Elena Vodarici; Maria Fulina; Daniela Pițigoi; Elena Mocanu; Beatrice Severin; Claudia-Simona Cambrea; Irina-Magdalena Dumitru (Microorganisms, 2026)
Healthcare-associated infections (HAIs) caused by multidrug-resistant Klebsiella spp. represent a critical and escalating global public health threat. Carbapenem-resistant Klebsiella pneumoniae (CRKP) has been designated a critical-priority pathogen by the World Health Organization, and in the 2024 WHO Bacterial Priority Pathogens List, it was the top-ranked pathogen overall. The convergence of carbapenem resistance with hypervirulence in emerging strains has further complicated therapeutic decision-making. This review provides a narrative synthesis of the evidence published between 2020 and 2025 on the prevalence, resistance mechanisms, molecular epidemiology, clinical outcomes, and therapeutic strategies for Klebsiella pneumoniae infections acquired in healthcare settings, with particular attention to the Eastern European and Romanian context. PubMed/MEDLINE, Embase, Web of Science, and the Cochrane Library were searched for relevant publications from January 2020 to June 2025, supplemented by WHO and ECDC surveillance reports. Studies were selected narratively for their relevance to the themes addressed. No new quantitative pooling was undertaken; all summary estimates reported below are cited from the published meta-analyses and surveillance reports that generated them. In the most recent global meta-analysis of hospital-acquired CRKP infection, which pooled 61 studies and 513,307 patients from 14 countries, the global prevalence of CRKP among nosocomial K. pneumoniae infections was 28.69% (95% CI: 26.53–30.86%), with pronounced regional variation from 14.29% in high-income North America to 66.04% in South Asia, and 42.05% in Western Europe. Pooled mortality among patients infected with CRKP has been estimated in a separate meta-analysis at 42.14%, compared with 21.16% among patients infected with carbapenem-susceptible strains, rising to 54.30% in bloodstream infections. Surveillance data place Romania third in Europe for carbapenem resistance among invasive K. pneumoniae isolates, at 50.30%, with a distinctive predominance of NDM plus OXA-48-like co-producers. Ceftazidime-avibactam is recommended for KPC- and OXA-48-producing strains, whereas metallo-beta-lactamase producers require aztreonam-containing combinations. CRKP in HAIs constitutes a global epidemiological emergency characterised by marked regional heterogeneity in carbapenemase distribution, high attributable mortality and rapidly evolving molecular profiles. Locally adapted surveillance, rapid molecular diagnostics, and stewardship programmes are required since empirical therapy cannot be standardised across regions.